(untitled) (Revista científica Olimpia, 2019)
The present investigation was implemented with the aim of applying a System of actions for the stimulation of executive functions cognitive flexibility and inhibitory control of behavior. For this purpose, a cross-sectional, descriptive-correlational study was used, through a quantitative research design, in athletes of the rhythmic gymnastics school selection in Granma province. We used the Wisconsin Sorting Cards Test (WSCT) or Wisconsin Card Draw and the Stroop Test, included in the SESH 1.1 version to evaluate cognitive flexibility and inhibitory behavior control, respectively; which were used at the beginning and at the end of the evaluation. In the processing of the data information, the SPSS software package version 21.0 was used, descriptive statistical tests such as frequency distribution, mean, dispersion test as range and standard deviation. The results obtained show statistically significant changes in the athletes demonstrating the effectiveness of the System of actions implemented to stimulate said executive functions.